2022
DOI: 10.1021/acsanm.2c00990
|View full text |Cite
|
Sign up to set email alerts
|

Self-Powered Photoelectrochemical Photodetectors Based on Electrochemically Exfoliated In2Se3 Nanosheets

Abstract: Two-dimensional (2D) In2Se3 has received considerable attention due to its suitable band gap, good photoresponse, and high stability, making it a good candidate for high-performance photodetectors. Self-powered 2D In2Se3-based photodetectors consisting of heterojunctions usually require a complex fabrication process, hindering their application. In this work, we synthesize 2D In2Se3 nanosheets by an electrochemical exfoliation method and fabricate self-powered In2Se3 photoelectrochemical (PEC) photodetectors b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…After 1 month of storage, the photoswitching is stable and J ph decreases from −7.92 to −7.9 μA/cm 2 (Figure b), demonstrating the excellent long-term stability of 2D CuO-based PEC PDs. Compared with previous studies, , 2D CuO NSs PEC PDs show excellent multicycle stability and good long-term stability (more details in Table ), which provide a solid foundation for practical applications. The weak decline in the photoresponse originates from the erosion of the CuO photocathode in the solution. , The stability could be further improved by surface coating.…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…After 1 month of storage, the photoswitching is stable and J ph decreases from −7.92 to −7.9 μA/cm 2 (Figure b), demonstrating the excellent long-term stability of 2D CuO-based PEC PDs. Compared with previous studies, , 2D CuO NSs PEC PDs show excellent multicycle stability and good long-term stability (more details in Table ), which provide a solid foundation for practical applications. The weak decline in the photoresponse originates from the erosion of the CuO photocathode in the solution. , The stability could be further improved by surface coating.…”
Section: Resultsmentioning
confidence: 84%
“…The calculated D * values are 9.1 × 10 8 , 6.9 × 10 8 , 5.4 × 10 8 , 2.9 × 10 8 , and 0.85 × 10 8 Jones for 365, 455, 525, 630, and 850 nm light illumination with a power intensity of level I, respectively (more details in Table S6). The photoresponse of CuO PEC PDs not only surpasses most 2D material-based broadband PEC PDs but also outperforms some traditional solid-state CuO-based PDs ,,, (more details in Table S7).…”
Section: Resultsmentioning
confidence: 99%
“…Most importantly, the intrinsic working principle coupled with additional surface modifications of the PEC photodetector enables low-cost, high-efficiency and versatile UOC applications by directly working in aqueous electrolyte environments. Previ-ously, we have explored different surface decoration strategies, including Pt, [10,11] MoS x , [16] Co 3 O 4 , [61] Rh/Cr 2 O 3 [12] and RuO x [62] to enhance the device performance of PEC photodetector or to achieve dual-polarity photoresponse behavior, [61][62][63][64] herein, we mainly explore the application of such PEC photodetector with simultaneous improvement of responsivity and response speed for possible UOC, [9,61] with a proof-of-concept demonstration.…”
Section: Proof-of-concept Demonstration Of Uoc With 3 Db Bandwidth Ov...mentioning
confidence: 99%
“…Recently, In 2 Se 3 , a member of group III–VI 2D semiconducting materials, has attracted increasing attention due to its diverse phases (α, β, γ, δ, κ, etc. ), excellent electric, ferroelectric, piezoelectric, photoelectric, and thermoelectric properties . Among all phases of In 2 Se 3 , α-In 2 Se 3 is recognized as the most stable layered structure at room temperature, and it demonstrates robust ferroelectricity for both in-plane and out-of-plane directions even when thinning down to a monolayer .…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Figure 4a,b, a rise time of 16.3 ms and a decay time of 18.3 ms were obtained under 447 nm laser illumination, comparable with previously reported photodetectors in In 2 Se 3 . 29,31,32 Figure 4c,d shows the excitation wavelength dependence plots for rise time and decay time. It is found that there is a large variation in response time as the excitation wavelength approaches 808 nm, i.e., the near-infrared region.…”
Section: ■ Introductionmentioning
confidence: 99%